Implementing Fuzzy Logic to Forecast Electricity Usage Costs - Ade Riyanti; Arda Dwiyana; Danar Restu Firdaus; Danke Hidayat; Fajri Haykal Rahman; Muhammad Rafi Ari Ghani; Agung Prayudha Hidayat; Dwi Yulinar Chairunisa (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
Electricity has a very vital role in human life, being a form of energy that is inseparable from various aspects of daily activities. The greater the use of electricity will have an impact on increasing the cost of electricity use. By applying fuzzy logic methods, research focuses on understanding the efficiency of electrical power use, identifying key factors that affect efficiency at the household level. This study aims to apply the Mamdani method in fuzzy logic to predict the cost of electricity consumption and measure the level of accuracy of the implementation of fuzzy logic. The variables used as the basis of the study involved house size, electronic equipment, electrical power, economic income, and electricity usage cost. The implementation of this research will use Matlab software because it provides various tools for the Mamdani method. The results of the implementation of fuzzy logic with the Mamdani method for the example case analyzed in obtaining electricity usage cost that needs to be paid is Rp. 455,500. Thus, these results indicate that the Mamdani method in fuzzy logic is effectively used to predict electricity usage cost in Leuwimekar Village, Bogor City.